2019
DOI: 10.15537/smj.2019.4.24010
|View full text |Cite
|
Sign up to set email alerts
|

Association of acute stress with multiple sclerosis onset and relapse in Saudi Arabia

Abstract: Objectives: To determine if there is a relationship between acute stress and either the onset or relapse of multiple sclerosis (MS) and to discover how different types of acute stressors may be involved. Methods: This study was carried out in Saudi Arabia between September 2017 and June 2018 and involved King Fahad University Hospital in Eastern province, Arfa Multiple Sclerosis Society in the Central and Western province of Saudi Arabia. A cross-sectional descriptive s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 13 publications
(12 reference statements)
1
8
0
Order By: Relevance
“…A previous study concluded that most MS patients' relationships with partners, children and close friends were happy and healthy, factors which have an impact on mental health [22]. Being married was associated with a good prognosis in terms of disease progression [23]. These findings are consistent with our findings showing a significant difference in social status, in that people who were widowed, divorced, and separated had significant depressive symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…A previous study concluded that most MS patients' relationships with partners, children and close friends were happy and healthy, factors which have an impact on mental health [22]. Being married was associated with a good prognosis in terms of disease progression [23]. These findings are consistent with our findings showing a significant difference in social status, in that people who were widowed, divorced, and separated had significant depressive symptoms.…”
Section: Discussionsupporting
confidence: 91%
“…Third, the current study was based on subjective assessment and self-reporting of fatigue and thus was not able to identify its clear causes whether it was simply due to MS complications such as sleep disorders, endocrine dysfunction, and mood disorders, or rather a primary MS fatigue ( 22 ). Finally, this study did not take into account the role of social support on coping strategies for MS patients, which might affect the quality of the results ( 21 ).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that up to 90% of pwMS had symptoms of fatigue, whereby they defined fatigue as tiredness, low energy, or exhaustion, and that these symptoms might be triggered by activities or increased temperature ( 11 , 12 , 14 ). Factors contributing to fatigue may include the individual presentation of the disease, some treatment side effects, functional status impairment, weakness, pain, and nocturia ( 21 ). Moreover, a study by Ayache and Chalah reviewed various causes of fatigue in pwMS which included anemia, vitamin-deficiencies, endocrine disorders, sleep disorders, psychiatric comorbidities, psychological burden, and medication side effects ( 22 ).…”
Section: Introductionmentioning
confidence: 99%
“…Stressful events, such as natural disasters and certain life events, have been proven to induce immunological alterations (22)(23)(24), which led us to speculate that stress caused by the COVID-19 pandemic (25) could impact the course of MS. However, in this study, we observed a significantly increased relapse rate only in patients who experienced treatment disruption due to COVID-19, not in patients who received continuous treatment or who had no immunotherapy.…”
Section: Discussionmentioning
confidence: 99%